New enzyme based process direction to prevent wool shrinking without substantial tensile strength loss - Lenting, H. (2006)
In this paper a new enzymatic process direction is described for obtaining machine washable wool with acceptable quality. In general, application of protease enzyme technology in wool processing results in considerable loss of tensile strength by diffusion of the enzyme into the interior of wool fibers. To overcome this disadvantage enzymatic activity has been more targeted to the outer surface of the scales by improving the susceptibility of the outer surface scale protein for proteolytic degradation. This has been realized by a pretreatment of wool with hydrogen peroxide at alkaline pH in the presence of high concentrations of salt.